The semiotics of Garin Nugroho’s photopoetry: a meta-philosophical approach / Maszalida Hamzah - Hamzah, Maszalida (2008)
Film is a magical medium of illusion in which the human is the magic. In this magical realm, we find ‘secret chambers’ that opens its doors to the key of ignition where the phenomenal as well as the transcendental is mirrored, those that reflect stories of our own, of others and of the hidden that is manifested. Nonetheless, the existence of film has always been seen as secondary to all other arts (painting, literature, theatre). As hybridity comes into play and the digital realm made its entry into the medium of film, the quest to find its own existence seemed inevitable. This thesis seeks to transcend the identity of film and filmmakers beyond what it is perceived to be; a mirror, those that reflect, represent, mimic, validate and affirm reality. To be seen as a comprehended tool, film has been discoursed in Plato’s theory of film, in Munsterberg’s theory of the film equals mind, in Bazin’s purity and spirituality, in the semiotician’s world of Saussure, Metz and Eco, in its constant act of becoming by Bergson. It is the intention of the researcher to invoke the essence of film in its poetic form, those that has only been mentioned in the works of Andrei Tarkovsky, Paolo Pasolini, Arthur Dovzhenko, Abbas Kairostami, Bresson, Ozu, Zhang Yi Mou, Hou Hsiao Hsien that is consumed and produced. By the methodic element of philosophical interpretation, it seeks to place film as a photo-poetry, created by the filmmaker as the Photo-poet. A discourse on Maya Deren’s film poem, Tarkovsky’s Sculpting in Time, Pasolini’s Cinema of poetry, Kant’s transcendentalism, Deleuze’s time-image and the film style of the montagist, realist, avant-garde as well as the Figural will also be highlighted. This is backed by philosophical writings of Santayana, Cavell, Plato, Aristotle and analysis of Garin Nugroho’s films. This research has finally proven that the films of Garin Nugroho is a photo-poetry and that it is the product of a photo-poet as discussed in Chapter 4. Based on this, the researcher is able to form the characteristics of a photo-poetry being; Pure, Transcendent/ Spiritual, Artistic and I-ness.